Heterosis breeding in pepper with use of lines originated by distant crossing - A. R. Bukharov; A. F. Bukharova (Овощи России, 2009)
Hybrids were originated by diallelic crossing of seven lines created by introgression selection. The features of inheritance of quantity locus traits were studied. The promising hybrids were distinguished from standard ones by a higher yield at early-term harvesting 0.1-0.5 kg. on square meter as well as for total harvesting 1.1 1.9 kg. on square meter.